A Study of the AMIN Vision and Mission From the Perspective of Mohammad Natsir (A Case Study of the 2024 Presidential Election) - Muhamad Fajar Pramono; Mohammad Latief; Afifah Fauziah; Adzkia Fityatul Mujahidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research focuses on analyzing the vision, mission and work program of Anies Baswedan and Muhaimin Iskandar through the lens of Mohammad Natsir's thoughts which are full of Islamic teachings. This study aims to examine whether the vision, mission, and work programs of Anies Baswedan and Muhaimin Iskandar contain elements of Islamic religious values. Given the number of Indonesian people reaching 86.7% who adhere to Islam more than other religions, the values of Islamic teachings are in the spotlight. This research is qualitative research with a case study approach. The data analysis will go through three important steps, namely data reduction, data display and data conclusion. This study found that the implementation of Islamic principles is very visible in the vision and mission of Anies Baswedan and Muhaimin Iskandar. By referring to the concept of maqashid shari'ah and direct observation of the conditions of Indonesian society in its various regions, this pair succeeded in outlining ideas that are expected to improve welfare and unite all Indonesian people. In their vision and mission, there is a system of government that is in line with Moh. Natsir's thinking. The concept of democracy emphasized by Natsir, which includes principles such as justice, the rejection of exploitation and poverty, the use of wealth for the benefit of society, and deliberation in decision-making processes that affect the people, appears to be reflected in Anies Baswedan and Muhaimin Iskandar's views on state development and organization.